Development communication sourcebook : - Mefalopulos, Paolo (World bank, 2008)
This Sourcebook highlights how the scope and application of communication in the development context are broadening to include a more dialogic approach, one that facilitates assessment of risks and opportunities, prevents problems and conflicts, and enhances the results and sustainability of projects when implemented at the very beginning of an initiative. The book presents basic concepts and explains key challenges faced in daily practice. Each of the four modules is self-contained, with examples, toolboxes and much more.